Mucopyocele of the maxillary sinus - Avinash Kshar; Abhijeet Patil; Hemant Umarji; Sonali Kadam (Wolters Kluwer Medknow Publications, 2014)
Mucoceles are defined as chronic, cystic lesions in the paranasal sinuses. When the mucocele content becomes infected, the lesion is defined as mucopyocele. Most mucoceles are located in the frontal and anterior ethmoid sinuses and normally they involve the frontal-ethmoid complex, expanding to the superior-medial region of the orbit, leading to ocular disorders; maxillary sinus presentation is rare. In the present article, the authors described a rare case of mucopyocele in the maxillary sinus.